2013
DOI: 10.1021/ol401775t
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Oxidative Cyclization of Arylphosphonic Acid Monoethyl Esters with Alkenes: Efficient Synthesis of Benzoxaphosphole 1-Oxides

Abstract: Rhodium-catalyzed tandem oxidative alkenylation and an intramolecular oxy-Michael reaction were developed using arylphosphonic acid monoethyl esters and alkenes under aerobic conditions, which produced benzoxaphosphole 1-oxides in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 80 publications
2
13
0
Order By: Relevance
“…Accordingly, we recently developed synthetic approaches to cyclic phosphonates via phosphoryl group‐directed CH activation: Rh‐catalyzed activation/Michael reaction using phosphonic acids and activated alkenes [Eq. (1), Scheme ],7 Pd‐catalyzed CH activation/cyclization of aryl‐ and benzylphosphonic acids [Eq. (2)],8 and Rh‐ or Ru‐catalyzed CH activation/annulations using phosphonic acids and disubstituted alkynes [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, we recently developed synthetic approaches to cyclic phosphonates via phosphoryl group‐directed CH activation: Rh‐catalyzed activation/Michael reaction using phosphonic acids and activated alkenes [Eq. (1), Scheme ],7 Pd‐catalyzed CH activation/cyclization of aryl‐ and benzylphosphonic acids [Eq. (2)],8 and Rh‐ or Ru‐catalyzed CH activation/annulations using phosphonic acids and disubstituted alkynes [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The carbonyl group also plays a key role in this reaction because no desired products were detected when imines were subjected to the standard reaction conditions (Scheme 6.8c). In the same year, a rhodium(III)-catalyzed cyclization by employing alkenes and arylphosphonic acid monoesters for the synthesis of benzoxaphosphole 1-oxides was reported by Lee and coworkers (Scheme 6.9) [17]. Using the combination of [RhCp*Cl 2 ] 2 as the catalyst and CH 3 CN as the solvent, the cyclization showed broad scope to both internal alkynes and arylphosphonic acid monoesters.…”
Section: Other Five-membered Oxygen-containing Heterocyclesmentioning
confidence: 99%
“…[127] They found that these compounds reactedw ith electron-deficient alkenesi nt he presence of aR h-catalyst, an oxidant (AgOAc) andabase (LiOAc), producing two products in an almoste quimolar ratio:a lkenyl product 156 and benzoxaphosphole 157.I ti sc lear that benzoxaphosphole 157 results from intramolecular oxa-Michael addition of 156.B ase and solvent screening led to optimized conditions in which only the desired benzoxaphospholene 157 was produced in 85 %i solated yield. [127] They found that these compounds reactedw ith electron-deficient alkenesi nt he presence of aR h-catalyst, an oxidant (AgOAc) andabase (LiOAc), producing two products in an almoste quimolar ratio:a lkenyl product 156 and benzoxaphosphole 157.I ti sc lear that benzoxaphosphole 157 results from intramolecular oxa-Michael addition of 156.B ase and solvent screening led to optimized conditions in which only the desired benzoxaphospholene 157 was produced in 85 %i solated yield.…”
Section: Transition-metal-catalyzedcyclization Reactionsmentioning
confidence: 99%
“…In 2013, the group of Lee reported on the CÀHa ctivation of o-tolylphosphonic acid monoethyl esters 155 (Scheme 38). [127] They found that these compounds reactedw ith electron-deficient alkenesi nt he presence of aR h-catalyst, an oxidant (AgOAc) andabase (LiOAc), producing two products in an almoste quimolar ratio:a lkenyl product 156 and benzoxaphosphole 157.I ti sc lear that benzoxaphosphole 157 results from intramolecular oxa-Michael addition of 156.B ase and solvent screening led to optimized conditions in which only the desired benzoxaphospholene 157 was produced in 85 %i solated yield. Substrate scope determination revealed that av ariety of electron-deficient alkenes readily reacted to give the benzoxaphospholenes 157 in high yields.…”
Section: Scheme33 Transformation Of Allyl-disubstituted Oxaphospholementioning
confidence: 99%
See 1 more Smart Citation